Nonlinear Dynamics — 2010 - (:unkn) unknown (National Technical University "Kharkov Polytechnic Institute", 2010)
The book of Proceedings includes extended abstracts of presentations on the Third International conference on nonlinear dynamics dedicated to the 125-th anniversary of the National Technical University "Kharkov Polytechnic Institute" foundation.

В сборник включены расширенные тезисы докладов 3-й Международной конференции по нелинейной динамике, посвященной 125-й годовщине со дня основания Национального технического университета "Харьковский политехнический институт".
Нелинейная динамика — 2010
Keywords: Dynamics of Discrete Systems; Dynamics of Distributed Systems; конференции НТУ "ХПИ"; труды ученых НТУ "ХПИ"; нелинейная динамика